Optical coherence tomography findings in beta-thalassemia major: a systematic review and Meta-analysis - Maryam Firdous; Muhammad Farooq Umer; Suriyakala Perumal Chandran (International Journal of Ophthalmology)
AIM: To describe the optical coherence tomography (OCT) findings of the retinal nerve fiber layer thickness (RNFLT) and choroidal thickness (CT) in beta-thalassemia major. METHODS: A systematic search was conducted on PubMed, Cochrane, and Embase using a combination of specific key words. The records found were screened in two phases (title/abstract, and full-text screening). All the original observational cross-sectional studies conducted on beta-thalassemia major cases and controls reporting the RNFLT and CT were included. The Meta-analysis was run for comparing the OCT measurements between beta-thalassemia cases and controls including pooled effect size, confidence intervals (CI), quality assessment, and publication bias. The measurements included were RNFLT (average, and in various quadrants), and CT. RESULTS: A total of 10 studies were included in this Meta-analysis including a total of 684 individuals, 362 cases and 322 controls. The RNFLT and CT showed a significant reduction in the values of beta-thalassemia cases as compared to controls. The heterogeneity among the included studies was found to be 92.65% for the average RNFLT and 30.13% for the CT making it obvious to use random effects model for analyzing the RNFLT values while fixed effects model for the CT. The Egger's test showed significant publication bias among all the parameters except for nasal RNFLT (P=0.507), and CT (P=0.281). The estimated average effect size for the average RNFLT was 1.04 (95%CI: 0.35 to 1.72, Z=2.961, P=0.003) and for CT was 0.74 (95%CI: 0.51 to 0.96, Z=6.523, P<0.001). CONCLUSION: This Meta-analysis concludes that the RNFLT and CT are significantly thinner in beta-thalassemia cases in comparison to healthy individuals. Therefore, the RNFLT and CT must be evaluated in routine clinical practice in order to avoid irreversible vision loss particularly in beta-thalassemia individuals.